The next three terms in the sequence are -3, 6 and 15.

You can find these by writing down the first term and then adding 3, 6 and 15 to this.

To do this we need to use the formula for adding a sequence:

a + (n – 1)d = a + d(n – 1)

So, if we want to find out what the next three terms are in the sequence above, we can use this formula with “a” as -3 and “d” as 3, 6 or 15:

-3 + (n – 1)d = -3 + 3d(n – 1)

-3 + 3 × (-1) = -3 + (-3) = -6

-3 + 3 × 2 = 9

-3 + 3 × 5 = 15

(Visited 5 times, 1 visits today)

Last modified: October 11, 2022